Effects of Time-Varying Magnetic Fields in the Frequency Range 1 kHz to 100 kHz upon the Human Body : Numerical Studies and Stimulation Experiment - Bohnert, Julia (Karlsruhe transactions on biomedical engineering / Ed.: Karlsruhe Institute of Technology / Institute of Biomedical Engineering, 2012)
In this work, the physiological effects of time-varying magnetic fields up to 100 kHz have been investigated, namely magnetic stimulation and body warming. Simulation studies were based on numerical calculations on sophisticated cell and body models. In addition, magnetic stimulation thresholds have been determined experimentally.The project was carried out within the scope of the development of Magnetic Particle Imaging, a new imaging technology for medical diagnostics.